The Effect of Beta Thalassemia Major on Anterior Cranial Base in Cephalometric Analysis: Systematic Literature Review - Firma Ayna Al Mardiyyah; Arya Prasetya Beumaputra; Sri Wahyuningsih Rais (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Background: Thalassemia is a group of hemolytic diseases caused by genetic disorders resulting from a decrease in the synthesis of the alpha or beta chains of hemoglobin (Hb). A particular craniofacial cephalometric picture is found in the form of mild skeletal class II clinical manifestations. The anterior cranial base becomes a benchmark or reference sector in the measurement of dentofacial structures on cephalometric radiographs because it is considered relatively stable throughout craniofacial growth. Objective: The purpose of this systematic literature review was to determine the effect of beta thalassemia major on the length of the anterior cranial base observed through cephalometric analysis. Methods: References were selected using the PubMed, Science Direct, and Google Scholar databases published from January 2007 to December 2021. The complete articles that met the inclusion and exclusion criteria were then assessed using the Critical Appraisal Skills Program bias assessment and summarized to obtain demographic data and the length of the patient's anterior cranial base in the journal. Results: This systematic literature review succeeded in synthesizing 6 journals consisting of case-control studies with low bias assessment results in 4 journals and moderate bias assessment in 2 journals. All journals in this systematic literature review stated that the length of the anterior cranial base in patients with beta thalassemia major was not much different from the control group seen in cephalometric analysis. Conclusion: There is no effect on the length of the anterior cranial base in patients with beta thalassemia major based on measurements on cephalometric analysis.